Synthesis of 2-Indol-3-ylbenzofulvenes through a Tandem Reaction Catalyzed by Cationic Gold(I) Complexes - Álvarez, Estela; Miguel, Delia; García-García, Patricia; Fernández-Rodríguez, Manuel A.; Rodríguez, Félix; Sanz, Roberto (Synthesis, 2012)
A new access to benzofulvenes bearing an indol-3-yl substituent at C-2 has been developed. Treatment of 3-propargylindoles possessing an additional hydroxy group at the other propargylic position with a cationic gold(I) complex triggers a tandem 1,2-indole migration/aura-iso-Nazarov cyclization/elimination sequence that takes place under mild conditions.
Keywords: benzofulvenes; catalysis; gold; indoles; tandem reactions